EFFECTIVENESS OF ‘STRUCTURED EDUCATIONAL PROGRAM’ ON KNOWLEDGE OF MINOR AILMENTS DURING PREGNANCY AND ITS MANAGEMENT AMONG PRIMI GRAVIDA MOTHER (International Journal of Food and Nutritional Sciences, 2021)
Minor disorders are defined as the discomforts associated with the pregnancy such as nausea,Vomiting, back pain, heartburn, pica, constipation, leg cramps, and varicose vein etc. A minor ailment is very common and is reported by 50%-80% of pregnant women. The healthy mother bring forth the healthy child. So many of minor disorders can be controlled and prevented using existing knowledge and affordable tools to the primi gravida mothers. A Quantitative research approach with “one group pretest and posttest design” was used in the study. 40 primi gravida antenatal women were selected by convenient sampling technique from CHC Kalyanpur. Structured Knowledge Questionnaire, were used for data collection.